1996
DOI: 10.1111/j.1467-9450.1996.tb00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pathways of behavior problems in the young child: factors associated with continuity and change

Abstract: The continuity and discontinuity of behavioral problems from age 4 through age 7 until 10 were examined in 120 children. The mothers rated childhood behavior problems at the three age points. Problems were defined as above 80th percentile. Individual transition classification of problematic and non-problematic children showed that 7% had stable behavior problems, 60% stable non-problematic behavior and the rest displayed transitions related to either onset or offset of problems. The mechanisms involved in onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Nevertheless, several caveats are necessary. There is good evidence that females are more likely than males to discuss emotional matters (Maccoby, 1998) and this applies to mothers' discussions with friends and colleagues about their children as much as it does to other aspects of emotional interchange (Borge, 1996). Accordingly, it is likely that, in general, mothers will know more than fathers do about their children's intimate thoughts and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several caveats are necessary. There is good evidence that females are more likely than males to discuss emotional matters (Maccoby, 1998) and this applies to mothers' discussions with friends and colleagues about their children as much as it does to other aspects of emotional interchange (Borge, 1996). Accordingly, it is likely that, in general, mothers will know more than fathers do about their children's intimate thoughts and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Contact with schools may also encourage some parents to become involved in educational programmes themselves (Briggs 1997). In the case of mother of young children, a Norwegian researcher suggests that maternal involvement in education may play a secondary prevention role in relation to childhood problems (Borge 1996). Schools may also serve as a conduit through which hardpressed parents can access group and other support relevant to their demanding circumstances (Greif 1994;Briggs 1997).…”
Section: School As a Resource To Parents And Communitiesmentioning
confidence: 99%
“…# 1998 Blackwell Science Ltd `promotion of other prosocial attitudes and behaviours, and the inculcation of a positive self image' (Mortimore 1995, p. 357). According to a Norwegian study of in¯uences on children's development, organized leisure opportunities ± to which school may frequently oer access ± may assist in preventing behaviour problems in children (Borge 1996). A study of children from non-harmonious homes has found that positive recognition for hobbies or activities is protective for such children (Jenkins & Smith 1990, p. 67).…”
mentioning
confidence: 99%
“…Research has found that spare time activities can help to develop a young person's social skills, social network, enhance self‐esteem and self‐efficacy and promote good mental health (Quinn 1995; Borge 1996; Gilligan 1999). Gilligan (1999, p. 187) states that ‘the progress and resilience of young people in public care can be greatly enhanced by attention to the value of cultural, sporting and other activities in their lives’.…”
Section: Introductionmentioning
confidence: 99%